2007
DOI: 10.1179/174329307x164274
|View full text |Cite
|
Sign up to set email alerts
|

Actual application of FEM to analysis of large scale mechanical problems in welding

Abstract: The finite element method is a powerful tool for predicting welding distortion. However, the mechanical phenomena are strongly non-linear and transient and thus, thermo-elastic-plastic finite element analyses of the phenomena require very long computational time. To overcome this problem, an interactive substructure method was developed as an approach to reduce the computational time in three-dimensional analyses. In this paper, in order to confirm calculation efficiency for a large scale problem, a pipe model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 6 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…The high efficient ISM is apt for the strong non-linear welding problem and the computation time can be reduced notably. [31][32][33] Finite element model Figure 1 shows the FE mesh of fillet welded joint used in this study, with a flange, 100061000628 mm, and a web erected on the flange plate, 1000640622 mm. Quadratic brick elements were used.…”
Section: Interactive Substructure Methodsmentioning
confidence: 99%
“…The high efficient ISM is apt for the strong non-linear welding problem and the computation time can be reduced notably. [31][32][33] Finite element model Figure 1 shows the FE mesh of fillet welded joint used in this study, with a flange, 100061000628 mm, and a web erected on the flange plate, 1000640622 mm. Quadratic brick elements were used.…”
Section: Interactive Substructure Methodsmentioning
confidence: 99%
“…In this linear equation system solution procedure, the global and local analyses are performed independently and iteratively. Iterative substructure method (Murakawa et al, 2005;Nishikawa et al, 2007) employs superposed global and local meshes. The two meshes are analyzed alternately under assumed enforced displacement and external force boundary condition on the global-local interface.…”
Section: Introductionmentioning
confidence: 99%
“…As for the thermal elastic-plastic finite element analyses, an in-house code was employed based on ISM (Iterative Substructure Method) [15,16] in this research, and the accuracy of our code is already revealed through the comparison with not only experiments but also other commercial codes, where the element type was set as linear [4,17,18]. In order to demonstrate the multi-pass welding numerically, the elements representing the filler metal in the groove were deactivated before the welding, and when the weld bead was deposited, the corresponding elements were activated [12].…”
Section: Methods For Analysismentioning
confidence: 99%